2011
DOI: 10.1074/jbc.m111.219782
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Activity and Cellular Localization of the Circadian Clock Protein FRQ

Abstract: Eukaryotic circadian clocks employ autoregulatory negative feedback loops to control daily rhythms. In the filamentous fungus Neurospora, FRQ, FRH, WC-1, and WC-2 are the core components of the circadian negative feedback loop. To close the transcription-based negative feedback loop, the FRQ-FRH complex inhibits the activity of the WC complex in the nucleus by promoting the casein kinases-mediated WC phosphorylation. Despite its essential role in the nucleus, most FRQ is found in the cytoplasm. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 54 publications
4
54
0
Order By: Relevance
“…Moreover, CK1a is activated by recruitment to FRQ. In this way, a single molecule of bound CK1a could phosphorylate in cis a large number of sites that are distributed all over the intrinsically disordered polypeptide chain of FRQ and also WCC that is recruited to the FFC 16,17,29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CK1a is activated by recruitment to FRQ. In this way, a single molecule of bound CK1a could phosphorylate in cis a large number of sites that are distributed all over the intrinsically disordered polypeptide chain of FRQ and also WCC that is recruited to the FFC 16,17,29 .…”
Section: Resultsmentioning
confidence: 99%
“…FRH is essential for the viability of Neurospora owing to its function in RNA metabolism 14 . In addition, FRH has been implicated in a variety of non-essential, clock-related functions: FRH is crucial for cytoplasmic localization and turnover of FRQ 15,16 , and also for the interaction of FRQ with the circadian transcription activator White Collar Complex (WCC) 15,17 . Furthermore, it was reported that FRH mediates turnover of frq RNA by committing the messenger for degradation by the exosome 14 .…”
mentioning
confidence: 99%
“…Interestingly, this dual effect of ZTL on GI is reminiscent of the relationship between FREQUENCY (FRQ) and an RNA helicase (FRH) in the Neurospora clock. The formation of a FRQ-FRH complex (FCC) helps stabilize and retain FRQ in the cytosol, with increased FRQ nuclear levels when the interaction is disrupted or FRH levels are low (Cha et al, 2011). Conversely, the mammalian clock component mCRY helps retain the nucleocytoplasmic protein mPER2 in the nucleus and away from ubiquitylation and degradation in the cytosol (Yagita et al, 2002).…”
Section: Ztl-mediated Stabilization and Cytosolic Retention Of Gimentioning
confidence: 99%
“…Despite the presence of the nuclear localization signal, most FRQ protein is cytoplasmic, suggesting that there is an active process to export FRQ from the nucleus. Using FRQ deletion mutants, the C-terminus of FRQ that includes the FRQ/FRQ-interacting RNA helicase (FRH) interaction domain was found to play an important role for cytoplasmic localization of FRQ (Cha et al ., 2011). Other domains in FRQ include a casein kinase I (CK1) interaction domain located in the middle of the protein (Guo et al ., 2010) and two PEST domains that function in FRQ turnover (Görl et al ., 2001).…”
Section: The Genetics and Biochemistry Of The Frq/wcc Feedback Loopmentioning
confidence: 99%